UTILIZATION OF FISH OIL TO REDUCE THE RISK OF CARDIOVASCULAR DISEASE - Yasmin, Alya; Zahra Setiawan, Binta Febriana; Indriyani, Tutut Rizki; Saryono, Saryono (International Journal of Biomedical Nursing Review, 2022)
Introduction: Omega-3 fatty acids are found in fish oil. Omega-3 fatty acids play a role in the primary and secondary prevention of cardiovascular disease. Cardiovascular disease (CVD) is the leading cause of death in both developed and developing countries. Cardiovascular is a disease group that includes coronary heart disease (CHD), cerebrovascular disease, peripheral artery disease, rheumatic heart disease, deep vein thrombosis, and pulmonary embolism. Purpose: This systematic review aims to identify the prevention of cardiovascular events using fish oil. Methods: This journal was obtained from the Google Scholar, Pubmed, and Science Direct databases, which then extracted the data by looking at all the selected publication articles. Results: This reviewed journal shows the beneficial effects of fish oil in reducing mortality from cardiovascular disease. Omega-3s show benefits for preventing cardiovascular disease because omega-3s can reduce blood platelets and thus prevent the clogging of arteries. Discussion: Arterial blood vessels are at risk of obstructing blood flow to the heart. Conclusion: Thus, it can be concluded that fish oil can reduce the risk of cardiovascular disease.